Food Simulating Organic Solvents for Evaluating Crosslink Density of Bulk Fill Composite Resin - Neveen M. Ayad; Hala A. Bahgat; Eman Hussain Al Kaba; Maryam Hussain Buholayka (International Journal of Dentistry)
Objectives. To evaluate crosslink densities of two bulk fill composite resins and determine if the used Food Simulating Organic Solvent (FSOS) affected them. Methods. Forty specimens were prepared from SureFill and SonicFill bulk fill composite resins, 20 each. All specimens were stored dry for 24 h. Each group was divided into 2 subgroups: stored in ethanol (E) 75% or in methyl ethyl ketone (MEK) 100% for 24 h. Crosslink density was evaluated by calculating the difference between the Vickers hardness numbers of the specimens stored dry and after their storage in FSOS. The data were statistically analyzed using t-test. Results. The means of crosslink density in E and MEK were 6.99% and 9.44% for SureFill and 10.54% and 11.92% for SonicFill, respectively. t-test displayed significant differences between crosslink densities of SureFill and SonicFill: (P<0.0001) in E and (P=0.02) in MEK and between crosslink densities of SureFill in E and MEK (P=0.02). Conclusions. Crosslink density of bulk fill composite resin can be evaluated using E or MEK. SureFill has higher crosslink density than SonicFill in both E and MEK.